Shaping Design Layout of a Combined Insertion Module with Chemical Acceleration and Electric Cruising Units in Creo Elements/Pro Environment. (2017) - Petrukhina, K.V.; Russkikh, A.S.; Salmin, V.V.; Safronov, S.L.
Abstract: The paper considers shaping the design layout of a combined insertion module, with chemical acceleration unit and electric propulsion cruising unit, intended to deliver payload to geostationary orbit, in the three dimensional design environment Creo elements/Pro. The result of the work are the design layout of an insertion module, including DM-03 chemical and electric propulsion cruising thrusters, satisfying the requirements set by the Angara A5 carrier and its nose cones.